Inovasi Birokrasi : Perspektif Analisis Hybrid Teori - Lesmana Rian Andhika (Jurnal Borneo Administrator, 2018)
This research attempts to illustrate, identify and disclose some relevant scientific literature findings to construct a theoretical conceptual concept of bureaucratic innovation; How conceptual theorists of other sciences can build the concept of bureaucratic innovation to achieve an understanding of bureaucratic innovation more holistically with hybrid models. The meta-theory method (the analysis of theory) is used, the literature and documents nationally and internationally are traced deductively. Results of this study reveals that hybrid theory allows the possibility that bureaucratic innovation can be elaborated from various disciplines of science. Hybrid theory model can explain various assumption that exist in bureaucracy. however, hybrid concept needs to be tested with empirical approach in order to be more coherent and constructive. Therefore, this research can be a source of limited theoretical conceptual knowledge of bureaucratic innovation outlined from some of the existing scientific literature. Keywords: bureaucracy, innovation, hybrid model AbstrakPenelitian ini lebih berupaya untuk mengambarkan, mengidentifikasi dan mengungkapkan beberapa temuan literatur ilmiah yang relevan untuk membangun konseptual teoritik inovasi birokrasi. Bagaimana konseptual teoretik dari ilmu pengetahuan lain dapat membangun konsep inovasi birokrasi agar mencapai pemahaman tentang inovasi birokrasi lebih holistik dengan model hybrid. Metode meta-theory (the analysis of theory) digunakan, literatur dan dokumen secara nasional dan internasional ditelusuri secara deduktif. Hasil penelitian ini mengungkapkan, inovasi birokrasi bisa dielaborasi dari berbagai disiplin ilmu pengetahuan. Model hybrid theory memungkinkan untuk itu, model ini dapat menerangkan berbagai asumsi yang ada dalam birokrasi, lebih lanjut konsep hybrid perlu diuji dengan pendekatan empiris agar lebih koheren dan konstruktif. Oleh sebab itu penelitian ini dapat menjadi sumber pengetahuan tentang konseptual teoritis inovasi birokrasi yang terbatas diuraikan dari beberapa literatur ilmiah yang ada. Kata kunci: birokrasi, inovasi, hibrid model